Present-day activity and seismic potential of the north Qinling fault, southern ordos block, central China, as revealed from GPS data and seismicity - Yang, Chenyi; Ji, Lingyun; Yang, Yihai; Su, Lina; Wang, Ying; Shi, Huiren (Frontiers in Earth Science, 2023)
The North Qinling Fault, located at the boundary of the North China Block and the South China Block, represents an important tectonic structure between the Weihe Basin and the Qinling Mountains, and controls the subsidence and expansion of the Weihe Basin. This fault has been highly active and has caused strong earthquakes since the Holocene and in a pre-seismic stage currently, as indicated by the many paleoearthquake traces found along it. To determine the present-day activity and seismic potential of the North Qinling Fault, by inverting GPS data, we produced fault locking depth, slip rate, and regional strain fields maps; moreover, based on seismicity, we produced a seismic b-value map. Combining this information with modern seismicity, we were able to comprehensively analyze the seismic potential of different fault segments. Our inversion of GPS data showed that the slip rate of the western segment of the fault (Qingjiangkou–Xitangyu) and the correspondent locking depth are 1.33 mm/a and 13.54 km, respectively, while the slip rate of the middle segment (Xitangyu–Fengyukou) and the correspondent locking depth are 0.45 mm/a and 8.58 km, respectively; finally, the slip rate of the eastern segment (Xitangyu–Daiyu) and the correspondent locking depth are 0.36 mm/a and 21.46 km, respectively. The locking depths of the western and middle segments of the fault are shallower than 90% of the seismic cutoff depth, while the locking depth of the eastern segment of the fault is similar to 90% of the seismic cutoff depth, indicating that “deep creep” occurs in the western and middle segments, while the eastern segment is locked. Modern small earthquakes have involved the western and middle segments of the fault, while the eastern segment has acted as a seismic gap with weak seismicity, characterized by a higher shear strain value and a lower b-value. These characteristics reflect the relationship between the locking depth and seismicity distribution. The results of our comprehensive analysis, combined with field geological surveys, show that the eastern segment of the North Qinling Fault has a strong seismic potential and is presently locked.